Assessment of the epilepsy treatment gap in two cities of south-east of Brazil - Noronha,Ana Lúcia Andrade (2004)
OBJECTIVE: To assess the epilepsy treatment gap in Campinas and São José do Rio Preto, two cities in the State of São Paulo, Brazil. METHOD: The treatment gap was estimated using the formula n1-n2/n1x100, where n1 was calculated using 1.86% prevalence and represented the number of individuals with epilepsy, while n2 represented the number of people who could be treated with an adult standard dose for a year utilizing the antiepileptic drugs supplied by the public health system. RESULTS: Our estimates revealed that in 2001, approximately 50% of the population with epilepsy was treated with the recommended antiepileptic medication. CONCLUSION: These results suggest that a relevant percentage of patients with epilepsy are not untreated. Further epidemiological studies are needed to investigate the reasons for this treatment gap so that interventions can reduce this gap and improve the quality of life of patients with epilepsy.